(untitled) (Journal Of Educational and Psychological Researches, 2017)
The Islamic religion is a religion of tolerance and is pleased with worship and other legislation and the idea of peace is an authentic and profound idea related to the call for coexistence with all religions. The Prophet (PBUH) was keen to organize his relations with non-Muslims on the basis of cohabitation, On the basis of love and intolerance, God Almighty says: "If your Lord wants to make people one nation and they are still backward." Surah Hud: 118 Islam has taken care of the people and made them tolerant brothers who sympathize with their different beliefs. Which means that everyone has the right to live, believe and believe what he sees right and have the freedom to perform the acts of worship and beliefs he deems correct. The diversity of society is only a health condition that gives hope to the existence of beauty and life derived from the Almighty saying: (Oh people I created you from male and female and made you people and tribes to know each other)Surah Al - Khajrat